The Challenges of Constructing the Connectivity between Indonesia and Malaysia in the Malacca Strait - Awani Irewati (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2020)
Today, people have lived in one integrated space that make all their needs and activities can be served quickly and they become interdependent . In line with that, the implementation of connectivity concept within community, automatically, becomes inherent in their social and economic activities.Therefore, people need to construct connectivity in all activities. Even within the bigger community like ASEAN Community, people become more involved in a cohesive and competitive situation in order to fulfill the desired goals. Referring to one of President Jokowi's maritime development programs, namely